Pendekatan Diagnosis dan Tatalaksana Syringomyelia Sekunder dengan Komplikasi Gagal Nafas - Dzulfiqar; Fidha Ramayani; Ari Wahyuni (Medula, 2020)
Syringomyelia is a rare condition characterized by fluid-filled cavities called syrinx in spinal cord. Enlarging syrinx often cause progressive neurological damage, through combination of direct pressure on neural tissue and ischemia. Syringomyelia divided into primary and secondary based on it’s cause. More than half of secondary syringomyelia cases are caused by Chiari Malformation (CM) type I. Prevalence of CM is higher in children and younger adult than older adult. Diagnosis is effectively determined by Magnetic Resonance Imaging (MRI) and management are based on the main cause of syringomyelia. In this study, we describe a case in a 59 year-old women pesented with progressive weakness of all extremities for the past three months associated with respiratory failure. In physical examination we found flaccid type tetraplegia and absent of reflexes in all extremities. MRI result found syringomyelia from cervical 2 until 6 with MC type I. Foramen magnum decompression become primary management in syringomyelia caused by CM type I in order to return the abnormal flow of cerebrospinal fluid. Foramen magnum decompression in adults can improve the symptoms with minimal complication.